Patient Satisfaction and Body Image Following Mastectomy, Breast-Conserving Therapy, and Mastectomy With Reconstruction: A Study in Iran - Olfatbakhsh, Asiie; Haghighat, Shahpar; Tabari, Mohammadreza; Hashemi, Esmat; Sari, Fateme; Kaviani, Ahmad (Archives of Breast Cancer, 2018)
Background: Breast cancer is considered a chronic disease owing to the increases in survival rate. Thus, better body image and patient satisfaction with the surgery have become more important factors to be considered when choosing the surgical approach. The aim of this study was to compare body image and patient satisfaction following three different approaches. Methods: We evaluated 183 consecutive patients who had undergone three different surgeries including breast-conserving surgery (BCS), mastectomy, or mastectomy followed by reconstruction (M-R). Body image was evaluated using the BICI questionnaire, and patient satisfaction was rated using a multiple-choice question and a scale ranging from 1 to 10. Results: A significantly better body image was observed in the M-R and BCS groups compared with mastectomy (P = 0.02). In body image subscale analysis, social functioning scores were higher in the M-R and BCS groups than in the mastectomy group (P = 0.01), but no differences were obtained between surgery groups in appearance dissatisfaction subscale. Patients were more satisfied with BCS than the other two surgeries (P = 0.008). Conclusion: Based on the results of this study, it could be proposed that both oncoplastic BCS and implant reconstruction could provide patients with acceptable body image, while BCS could bring about better satisfaction with the surgery. Reconstruction may be an alternative for the patients to improve body image and satisfaction when BCS is not applicable.